Preparing Implementation of Transition Readiness Screening: What Do Paediatric Cancer Survivors and Caregivers Want? - Monarque, Marika; Buron, Laurianne; Granger, Nadège Gendron; Louis‐Delsoin, Wendy; Labonté, Nathalie; Provost, Carole; Rosberger, Zeev; Tsimicalis, Argerie; Bergeron, Élodie; Bonanno, Marco; Sultan, Serge; Laverdière, Caroline; et al. (Child: Care, Health & Development, 2025)
Background: Supporting transition from paediatric to adult healthcare is essential for the long‐term well‐being of paediatric cancer survivors. Guided by an implementation science approach, our overall programme of research seeks to integrate transition readiness screening in the routine care of paediatric cancer survivors, using the validated Transition Readiness Assessment Questionnaire (TRAQ). To plan for the screening implementation, the primary objective of this study was to first assess paediatric cancer survivors' current experiences with transition preparation and their preferences for screening and resources. A secondary focus group with parents was also conducted to complement youth perspectives. Methods: Focus groups were conducted with 14‐ to 18‐year‐old paediatric cancer survivors (n = 13) and parents (n = 6). Focus groups explored perceptions of care at the long‐term follow‐up clinic, transition preparedness, preferences for TRAQ administration (e.g., format, moment and location) and preferences for transition readiness resources. Interviews were analysed with an inductive thematic analysis approach. Results: This study identified several barriers to TRAQ implementation, including adolescents' lack of transition awareness, attachment to paediatric care and parental distress. Unclear TRAQ items were also noted as a challenge for adolescents. Strategies to address these barriers include regular discussions with healthcare providers, a comprehensive transition resource website, addressing emotional needs, providing parent guidance and offering flexible TRAQ administration options, for example, by leveraging technology (QR codes, choice of online or paper administration). Conclusion: This study highlighted the importance of addressing the informational and emotional needs of adolescents and parents for implementation, notably by engaging in discussions with clinicians and tailoring online transition readiness resources. Preferences and suggestions for TRAQ administration and resources will be integrated to align with patients and parents' needs and optimize implementation. Key Messages: The study identified key barriers to TRAQ implementation, including paediatric cancer survivors' lack of awareness of transition and understanding of the TRAQ, attachment to paediatric care and parental distress about long‐term follow‐up.Participants suggested strategies such as offering the TRAQ online, integrating it into wait times and enhancing awareness through individualized discussions.Addressing emotional needs through dedicated resources and incorporating discussions about transition‐related distress into the TRAQ implementation process is crucial.Participants preferred online resources over paper formats, and a webpage on transition resources was acceptable to both adolescents and parents.Results of this study are an essential first step in the preparation of a successful TRAQ implementation, with findings allowing better planning and adaptation of implementation to the local context and to adolescents and parents.